Economic methodology : understandings economic as a science - Boumans, Marcel (Palgrave, 2016)
"Economic Methodology explores the status and character of economics as a social science and introduces students to philosophical issues underlying modern science. Approaching the subject as philosophy of science for economists, the authors use the historical developments in philosophy of science to frame this introduction to the field of economic methodology. By doing this they strengthen students' understanding of economics as a science to enhance their reasoning skills, introducing them to the wider philosophical issues surrounding our understanding of the area"--